Bottom-up and top-down COBOL system migration to Web Services: An experience report [Thomson ISI, IF JCR2013=2] - Rodriguez, Juan Manuel (2013)
Moving from mainframe systems to Service-Oriented Architecture (SOA) using Web Services is an attractive but daunting task. The bottom-up or Direct Migration approach enables the effective modernization of legacy systems to Web Services. Conversely, bringing migration into fruition with the top-down or Indirect Migration approach is recognized as being comparatively harder but achieves better migration results. In practice, it is very uncommon to employ both approaches to the same large enterprise system, which leaves no room for comparison. This paper reports the outcomes of applying both migration approaches on a real COBOL system, presents the followed migration processes, their costs, and reports on the discoverability and reusability of target Web Services.